2011
DOI: 10.4161/gmic.2.3.15872
|View full text |Cite
|
Sign up to set email alerts
|

Purpose of recently detected inhibitory domain of theHelicobacter pyloriprotein CagA

Abstract: H elicobacter pylori infection is the most common bacterial infection worldwide and is strongly associated with gastric oncogenesis. Recently, we discovered that the H. pylori protein CagA, a risk factor for carcinogenesis, consists of two distinct membranetargeting domains. The C-terminal membrane-binding domain induces host cell responses associated with a high oncogenic potential. The N-terminal membrane-targeting domain, however, localizes to a different membrane substructure at the site of newly formed ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…The positively charged helix α18 (residues 610–639), harboring a surface-exposed cluster of conserved lysine/arginine residues at positions 613, 614, 617, 621, 624, 626, 631, 635 and 636, is believed to tether CagA to the negatively charged phosphate groups of the lipid membrane via electrostatic interactions [13, 16]. Although the first 200 amino acids of CagA have been shown to be sufficient for membrane tethering [35], regions 200–800 and 800–1216 were subsequently shown to also be important for membrane binding [36], leading to a hypothesis that two separate domains within the C-terminal region, spanning residues 200–800 and 800–1216, interact in trans to mediate interactions with the host cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The positively charged helix α18 (residues 610–639), harboring a surface-exposed cluster of conserved lysine/arginine residues at positions 613, 614, 617, 621, 624, 626, 631, 635 and 636, is believed to tether CagA to the negatively charged phosphate groups of the lipid membrane via electrostatic interactions [13, 16]. Although the first 200 amino acids of CagA have been shown to be sufficient for membrane tethering [35], regions 200–800 and 800–1216 were subsequently shown to also be important for membrane binding [36], leading to a hypothesis that two separate domains within the C-terminal region, spanning residues 200–800 and 800–1216, interact in trans to mediate interactions with the host cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…[95][96][97] Thus, it will be interesting to see if these results can be recapitulated in an infection model, especially since the levels of CagA are clearly different between these model systems. 77,89 One way to address these differences in model systems would be the creation of isogenic strains that could be used in a rodent model. Use of these same strains could then be expanded into a primate model as it is the closest model to replicate human disease.…”
Section: Cagamentioning
confidence: 99%
“…88 Thus, the conflicting results of the two previous studies were due to the particular region found in the truncated CagA products, which were different in each study. 88 Based on these results, Steininger, et al 89 have suggested the following model: the first 200 amino acids of CagA may serve as a membrane binding domain that is required to mediate proper CagA translocation into the host cell, targets CagA to cell-cell adhesions, and serves to inhibit EPIYAmediated cell signaling. Conversely, a second membrane targeting domain found in the C-terminus functions to tether CagA to the plasma membrane for EPIYA-mediated signaling events; both the N-and C-terminal regions of CagA interact with each other to accomplish membrane tethering.…”
Section: Cagamentioning
confidence: 99%
See 1 more Smart Citation
“…The N-terminal increases the rate and strength of the newly formed contacts between cells, diminishes cellular elongation and the construction of the apical membrane induced by the C-terminal and reduces the transcription activity of the TCF/ β catenin of the C-terminal. The former mediates the cell to cell adhesion by the E-cadherin-β catenin complex [5,35]. All this suggests that the N-terminal and the C-terminal also interact, and so influence the cellular response presented during the infection.…”
Section: Introductionmentioning
confidence: 99%